PROFESIONALISME KINERJA KEPALA LINGKUNGAN DALAM PELAYANAN PUBLIK DI KECAMATAN WENANG DI MASA PANDEMI COVID 19 - Steven W. Mongkau; Agustinus B. Pati; Evelin J. R. Kawung (Sam Ratulangi University, 2021)
This study aims to determine the professionalism of the neighborhood head in public services in Wenang District, Manado City, North Sulawesi Province during the Covid-19 pandemic. The data in this study were obtained by conducting observations and interviews and documentation with predetermined informants. The results showed that the unprofessional performance of the neigborhood head in Wenang District during the Covid-19 pandemic could be seen from several things, namely the lack of responsiveness, creativity and innovation of the neigborhood head in Wenang District. This is due to several factors, namely changes in work patterns during the COVID-19 pandemic, mastery of basic tasks and functions that are not optimal, leadership, education, mastery of technology and transportation, compensation and welfare and evaluation in terms of measurable performance.